INTERNET CONNECTED PATIENT HEALTHCARE MONITORING IN SMART PHONES - K., B.Sai Aravind; J., Mohana (International Journal of Psychosocial Rehabilitation, 2020)
Life expectancy has improved significantly in the past three decades thanks to major developments in scientific research and development, food and diet, healthcare, and environmental and personal health consciousness. As a consequence, the population growth in several countries is projected to increase exponentially over the coming years. Fast-growing numbers of the elderly are projected to have a detrimental effect on many countries' socio-economic policies in terms of the expenses associated with their wellbeing and wellness. Additionally, neurological, hair, digestive, skin, and mental wellbeing-associated illnesses are common across the globe. Most of such diseases may, however, be prevented and/or controlled adequately by continuous surveillance. Implementing continuous health surveillance and serving evolving health needs; it is critical to introduce effective, intrusive, and easy-to-use healthcare solutions. The ongoing prevalence of smart phones coupled with integrated sensors and sophisticated networking technologies makes them an enticing resource for ongoing and remote monitoring of human health and well-being. Within this article, we offer a thorough overview of advanced work and advances within smartphone-sensor-based safety technology. An analysis of legislative strategies for medical devices and their consequences for smartphone-based healthcare networks is discussed.